A Functionalist Approach to Democratic Innovations. Issue 4 (1st October 2020) - Jäske, Maija; Setälä, Maija
ABSTRACT: This article argues that it is important to analyse different democratic innovations in terms of their functions in democratic systems. For example, while citizens' initiatives have a role in agenda setting, practices of citizen deliberation should help collective will-formation and referendums facilitate collective decision making. The article provides a framework for the analysis of various instruments of direct, deliberative and participatory democracy based on their functions, and evaluates five democratic innovations from the perspective of this framework. It is pointed out that, when properly used, even advisory participatory instruments have a potential to improve the functioning of representative decision making. Moreover, the article shows how democratic innovations can functionally complement each other.